Lectotypifications in Millingtonia L.f. (Oroxyleae, Bignoniaceae) - Madhukar, Virendra K.; Srivastava, Sunil Kumar; Dubey, Nawal Kishore (Phytotaxa, 2016)
Millingtonia L.f. (Suppl. Pl. 1782: 45) was established by Linnaeus filius (1782) in the Supplementum Plantarum to honour Sir Thomas Millington (1628–1703), Sedleian Professor of Natural Philosophy, Oxford. This monotypic genus belongs to the plant family Bignoniaceae, tribe Oroxyleae (Olmstead et al. 2009).